2016
DOI: 10.1155/2016/7163615
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin Resistant Staphylococcal Bioaerosols in and around Residential Houses in an Urban Area in Central India

Abstract: Methicillin resistant staphylococci (MRS) commonly found in clinical samples or associated environment pose a major health challenge globally. The carriage rate of MRS in human population is high, especially in India but research on airborne distribution of MRS is scanty. The present study aimed to evaluate the prevalence of MRS in indoor and outdoor environment of residential houses. Air samples were collected using impactor air sampler. The total counts of viable bacteria, staphylococci, and MRS along with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Staphylococcus is one of the dominant genera among indoor airborne microbiomes both in hospital and other residential buildings [ 21 , 34 ]. The spread of multidrug resistant Staphylococci in environment from different sources has already been reported in India [ 30 , 35 37 ]. Furthermore, Staphylococci species such as MRSA and MR-CNSs are the biggest contributors in the spread of antibiotic resistant genes (ARGs) in the environment as reported from India and as well as from abroad [ 3 5 , 9 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus is one of the dominant genera among indoor airborne microbiomes both in hospital and other residential buildings [ 21 , 34 ]. The spread of multidrug resistant Staphylococci in environment from different sources has already been reported in India [ 30 , 35 37 ]. Furthermore, Staphylococci species such as MRSA and MR-CNSs are the biggest contributors in the spread of antibiotic resistant genes (ARGs) in the environment as reported from India and as well as from abroad [ 3 5 , 9 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, multi-drug resistant CNSs have been dominating in all kinds of microbiomes whether it is environmental samples, hospital-wastes, poultry, agricultural farms etc., thereby they are equally clinically relevant [ 15 , 36 , 42 ]. Recent study in India based on bioaerosols also showed the abundance of methicilin resistant Staphylococci in residential buildings in central India [ 37 ]. Yadav et al, have studied the abundance of bacterial and fungal loads in different residential indoor environments near and far from the Gwalior trade fair site [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…From massive traffic junctions of Dehradun city, India, airborne Micrococcus, Staphylococcus, and Bacillus bacterial species were identified in the percentage of 25.73, 17.98, and 13.8%, respectively (Madhwal et al, 2020). Furthermore, methicillin-resistant staphylococci (MRS) S. aureus (MRSA), coagulase-negative staphylococci (CNS) were identified in the airborne bioaerosols from India associated with global environmental health (Kumar and Goel, 2016).…”
Section: Bacterial Bioaerosolsmentioning
confidence: 99%
“…Previous studies have shown that the bioaerosols of indoor air in both livestock farming and hospital areas could carry MRSA strains and possibly act as a hotspot for spreading MRSA in the environment [ 10 , 11 ]. MRSA infection was primarily limited to persons directly associated with healthcare facilities with poor immune systems, which is called hospital-acquired MRSA (HA-MRSA) infection [ 12 ]. Later on, community-associated MRSA (CA-MRSA) infection was prevalent in healthy people who had never been hospitalized before.…”
Section: Introductionmentioning
confidence: 99%